2019
DOI: 10.2174/1871526518666180723152715
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Associated Risk Factors of Hyperglycemia and Diabetes Mellitus Among HIV Positive Patients in Tehran, Iran

Abstract: Hyperglycemia, especially pre-diabetes, is highly frequent among Iranian people living with HIV. Male gender, older age, prolonged duration of HIV infection, and higher BMI was associated with higher prevalence of hyperglycemia. Hence, it is important to screen all HIV infected patients at the time of diagnosis and then periodically for hyperglycemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 18 publications
2
11
0
Order By: Relevance
“…41 Advanced age, male gender, high BMI, and duration of living with HIV increase the risk of developing diabetes. 42 For the development of diabetes in PLWH, the mechanisms are multifactorial. A multicenter cohort study by Zhang et al 43 identified multiple plasma lipid species associated with diabetes, this association was enhanced in PLWH on ART.…”
Section: Discussionmentioning
confidence: 99%
“…41 Advanced age, male gender, high BMI, and duration of living with HIV increase the risk of developing diabetes. 42 For the development of diabetes in PLWH, the mechanisms are multifactorial. A multicenter cohort study by Zhang et al 43 identified multiple plasma lipid species associated with diabetes, this association was enhanced in PLWH on ART.…”
Section: Discussionmentioning
confidence: 99%
“…This is in contrast to the results of this study whereby no association between duration of infection and any comorbid condition was detected. Recently, an association between being a male, older age, prolonged duration of HIV infection, higher body mass index and higher prevalence of hyperglycemia was reported in Tehran [42] …”
Section: Discussionmentioning
confidence: 99%
“…Recently, an association between being a male, older age, prolonged duration of HIV infection, higher body mass index and higher prevalence of hyperglycemia was reported in Tehran. [ 42 ]…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of type 1 diabetes was estimated at 0.1% [ 54 ]. Studies on the prevalence of comorbidities among PLHIV in the Middle East and North Africa (MENA) region are currently lacking except for reports from Iran [ 55 ] whereby hyperglycemia was recently reported to be highly prevalent among a cohort of PLHIV. This study identified older age, male gender, higher BMI, and prolonged duration of HIV infection as associated risk factors [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies on the prevalence of comorbidities among PLHIV in the Middle East and North Africa (MENA) region are currently lacking except for reports from Iran [ 55 ] whereby hyperglycemia was recently reported to be highly prevalent among a cohort of PLHIV. This study identified older age, male gender, higher BMI, and prolonged duration of HIV infection as associated risk factors [ 55 ]. Recently, diabetes mellitus followed by dyslipidemia and hypertension was predominantly reported among a small group of HIV-infected individuals in western Saudi Arabia with age being a major risk factor [ 56 ].…”
Section: Discussionmentioning
confidence: 99%